Characterization of combustion process and emissions in a natural gas/diesel dual-fuel compression-ignition engine. (1st May 2021) - Kim, Wooyeong; Park, Chansoo; Bae, Choongsik
Highlights: Natural gas/diesel dual-fuel combustion process was studied in an optical engine. Color image segmentation in HSV space enables accurate separation of flame regimes. Larger natural gas content reduces diffusion flame with retarded flame development. Advanced injection shifts flame kernel outwards and produces rapid flame influx. Emission test verifies the flame visualization results with fuel supply parameters. Abstract: Dual-fuel (DF) combustion using natural gas and diesel has received considerable attention in the on- and off-road freight transportation sectors owing to its potential use in achieving better fuel economy and cleaner combustion. To determine the effect of the natural gas/diesel mixture quality on the combustion process and pollutant emission, high-speed flame visualization was used to investigate the phenomena of natural gas (NG)/diesel DF combustion in a 1.0 L optically-accessible single-cylinder engine. The diesel injection timing and natural gas substitution ratio (NGSR) were varied to implement diverse in-cylinder blending conditions under constant fuel energy input. A novel flame regime separation method based on color image segmentation in a hue-saturation-value (HSV) color space was used to quantitatively compare the spatial distributions of premixed and diffusion flame regimes. Because NG has a lower carbon content and higher auto-ignition resistance compared with diesel, the natural luminosity images for larger NGSRs revealed a significant reduction in the diffusion flame regime accompanied by retarded flame development. An earlier injection of the liquid diesel shifted the location of the early flame growth toward the piston bowl wall and created a rapid influx of propagating flame, while effectively suppressing the formation of intense soot radiation through longer ignition delay. These observations were verified by the exhaust emissions measured using the full-metal version of the engine and the same fuel supply parameters, specifically regarding the behavior of the smoke and nitrogen oxide emissions.